Generalized Fractional Integral Inequalities for MT-Non-Convex and pq-Convex Functions. (12th February 2022) - Wang, Wei; Haq, Absar Ul; Saleem, Muhammad Shoaib; Zahoor, Muhammad Sajid
Abstract : Fractional integral inequalities have a wide range of applications in pure and applied mathematics. In the present research, we establish generalized fractional integral inequalities for MT-non-convex functions and p q -convex functions. Our results extended many inequalities already existing in the literature.